Cooperativism, Autonomy and Power: the Cooperative Movement in Mexico during Cardenism - Nava Hernández, Eduardo; Barajas Pérez, Beny Oliver (Cooperativismo & Desarrollo, 2015)
Purpose: To expound and critically reflect upon the role of the cooperative movement in Mexico during the administration of General Lázaro Cárdenas del Río and his relationship with that movement. Description: The precedents for cooperativism arise starting with the Mexican Revolution and its fundamentally political use around the new regime; an exploratory analysis is presented of the cooperative project under Cardenism. Point of view: The political topic of cooperativism is reexamined as an instrument of hegemony of the new regime and how this had impacts on the workers of cooperativism; also the way in which the possibility of acquiring social leadership and becoming part of the dominant alliance during the developmental stage and in the current period of capitalist restructuring was diluted. Conclusions: The experience of the cooperative movement during Cardenism shows the need to socially and historically contextualize its action to determine its objectives and strategies in each period. Mexican cooperativism during the 1920s and 1930s shows how obtaining immediate advantages and advances can signify an inconvenient commitment in the long run for the autonomy of the cooperative movement, above all, if that development comes to an end.